The Independent and Dependent Variable: Influence on Jambi Province Rubber Exports - Septa Pratama; Adi Putra; Hasan Basri Hasan Basri (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2022)
Introduction/Main Objectives: This study was conducted to determine the effect of processed rubber production (X1), world rubber prices (X2), and exchange rates (X3) on the value of Jambi Province rubber exports (Y). The data in this study are secondary data sourced from the Jambi Central Statistics Agency for the period 2011-2021. Background Problems: The role of rubber exports is quite crucial for the economy of Jambi Province, apart from being a source of income, rubber exports also act as a promoter of regional development so that it is possible to create downstream effects for economic activities, especially the development of downstream industries. Research Methods: Several statistical tests were carried out, namely developmental analysis and regression analysis, to determine the effect of the independent variable on the dependent variable. Finding/Results: The research found that the world rubber price significantly impacted the value of rubber exports. In contrast, the production of processed rubber and the exchange rate had no significant effect on the value of rubber exports. However, simultaneous calculation results show that the production of processed rubber, world rubber prices, and the exchange rate significantly impact Jambi's rubber exports. Conclusion: From the analysis of the coefficient of determination, 82% of Jambi Province's rubber exports are influenced by processed rubber production, world rubber prices, and exchange rates, and other variables that influence the remaining 18%.